Understanding and controlling the self-healing behavior of 2-ureido-4[1H]-pyrimidinone-functionalized clustery and dendritic dual dynamic supramolecular network - Yang, Joo Ho; Lee, Junhaeng; Lim, Seayoung; Jung, Sunghoon; Jang, Soon Ho; Jang, So-hyun; Kwak, Seung-Yeop; Ahn, Seokhoon; Jung, Yong Chae; Priestley, Rodney D.; Chung, Jae Woo (ELSEVIER SCI LTD, 2019)
To optimize a dynamic network structure is a key feature for a supramolecular self-healing material capable of perfectly and repeatedly restoring its morphology and performance following a mechanically damaging event. Despite significant progress in self-healing supramolecular networks over the past few decades, many questions surrounding the dynamic responses of these networks during healing still remain. Herein, we present the selfhealing behavior of a dual dynamic supramolecular network (DDN) consisting of a weak clustery supramolecular network and a strong dendritic supramolecular network simultaneously. The DDN is easily prepared by the complexation of linear and non-linear poly(epsilon-caprolactone)s end functionalized with 2-ureido-4[1H]-pyrimidinone, which exhibits 100%-optical and 95%-mechanical healing efficiencies within 2 and 5 min, respectively, at 90 degrees C. In addition, the DDN film is shown to repeatedly self-heal ten times, even when damaged at the same position. DDN healing depends significantly on the density of the supramolecular network, and is specifically accomplished by the reassociation of hydrogen bonds between UPy moieties at the thermally swollen status of the dendritic network following the thermal disassembly of the clustery network. The DDN-coated nylon fabric exhibits excellent self-healing characteristics, which opens opportunities for creating scratch-protective materials.
Keywords: PI-PI STACKING; POLYMER BLEND; DESIGN; END